Seasonal variation in vascular dehydration risk: insights from the Kobe Orthopedic and Biomedical Epidemiologic (KOBE) study - Tomofumi Nishikawa; Naomi Miyamatsu; Aya Higashiyama; Yoshimi Kubota; Yoko Nishida; Takumi Hirata; Aya Hirata; Junji Miyazaki; Daisuke Sugiyama; Kazuyo Kuwabara; Sachimi Kubo; Yoshihiro Miyamoto; et al. (Komiyama Printing Co. Ltd, 2024)
Background: Dehydration, a risk factor for ischemic cerebrovascular diseases, is common in summer; however, the incidence of ischemic diseases is not necessarily higher in summer. Therefore, this study aimed to clarify the relationships between serum osmolarity, hematocrit, daily non-alcohol drink (NAD) intake and factors such as season and age as risk factors for dehydration. Method: Participants (703 women and 306 men) in the follow-up survey, in 2012 and 2013, of the Kobe Orthopedic and Biomedical Epidemiologic (KOBE) Study, consisting of healthy individuals living in Kobe, Japan, were categorized into two groups based on the examination month: the warmer and colder seasons. Multivariate analyses were conducted to examine disparities in serum osmolarity, hematocrit, and NAD intake between these two groups. Results: The colder season was found to be negatively correlated with serum osmolarity and NAD intake, but positively correlated with hematocrit, even after adjusting for relevant factors. Age was independently associated with serum osmolarity, but not with hematocrit and NAD intake. Conclusions: This study suggests that intra-vascular volume depletion is more likely in the colder season despite lower serum osmolarity compared to the warmer season. Age-related increases in serum osmolarity without a corresponding rise in water intake may contribute to this. These findings support the importance of addressing dehydration in the colder season, particularly in older adults.